A cross-linked polybenzimidazole anion exchange membrane and preparation method thereof

By grafting quaternary ammonium salts and flexible bication crosslinking agents in the polybenzimidazole anion exchange membrane to build a crosslinking network, the contradiction between ion conductivity and dimensional stability in the prior art is solved, and efficient ion conduction and mechanical performance are achieved.

CN119447390BActive Publication Date: 2025-04-01DONGHUA UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510033005.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-01
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

While improving the ionic conductivity, existing anion exchange membranes are prone to high water absorption and swelling, reducing their dimensional stability and mechanical properties, and at the same time, they have poor chemical stability under alkaline conditions.

Method used

A crosslinked polybenzimidazole anion exchange membrane was used to construct a membrane with high ion exchange capacity and good dimensional stability by grafting the structure of quaternary ammonium salt and flexible bication crosslinking agent.

Benefits of technology

It achieves high ionic conductivity, good dimensional stability, mechanical properties and chemical stability, and is suitable for anion exchange membrane electrolyzing water and fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447390B_ABST
    Figure CN119447390B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer electrolytes and ion exchange membranes, and relates to a cross-linked polybenzimidazole anion exchange membrane and a preparation method thereof. First, a long side chain piperidine quaternary ammonium salt and a flexible dicationic cross-linking agent are synthesized, and then 2,3-epoxypropyltrimethylammonium chloride or a long side chain piperidine quaternary ammonium salt and a dicationic molecular cross-linking agent are used to functionally modify polybenzimidazole, and finally a cross-linked polybenzimidazole anion exchange membrane is prepared by a solution casting method; or a cross-linked polybenzimidazole anion exchange membrane is prepared by a "post-cross-linking" strategy; the obtained product is simultaneously grafted with a cationic group and a flexible dicationic cross-linking agent on polybenzimidazole, and the balance between the ionic conductivity and the swelling rate of the anion exchange membrane is achieved. The long side chain piperidine cationic group and the cross-linking agent introduced by the present invention are both helpful in constructing an ordered microphase separation structure to form a network structure; the obtained product has high ionic conductivity and good dimensional stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer electrolytes and ion exchange membranes, and relates to a cross-linked polybenzimidazole anion exchange membrane and a preparation method thereof. Background Art

[0002] Under the threat of energy shortage and environmental degradation, the development of sustainable clean energy is becoming increasingly urgent. Therefore, the research on hydrogen energy conversion and utilization devices has received considerable attention and has become the focus of in-depth research. Among them, fuel cells are potential devices for using clean hydrogen energy to generate electricity through environmentally friendly and efficient electrochemical processes, while water electrolysis is a potential device for cleanly and sustainably decomposing water to produce hydrogen. Anion exchange membranes (AEMs), as one of the core materials of anion exchange membrane fuel cells (AEMFC) or anion exchange membrane water electrolysis (AEMWE), not only isolate the positive and negative electrodes to prevent gas crossover, but also conduct OH - And water molecules, isolating electrons.

[0003] Anion exchange membranes are mainly composed of polymer skeletons and cationic groups. The main problems of AEMs include the following three aspects: (1) Relatively low ionic conductivity. This is due to the low OH - Compared to H + The radius is large. Under the same conditions, the ionic conductivity is only H + 20~33% of the total ion conductivity. (2) The trade-off between ionic conductivity and dimensional stability. The direct way to improve the ionic conductivity of anion exchange membranes is to increase the ion exchange capacity, but this will lead to high water absorption and swelling of AEM, which will further reduce its dimensional stability and mechanical properties. (3) Under alkaline conditions, the cationic groups and polymer backbones in the anion exchange membrane structure may undergo chemical degradation, that is, the alkaline stability is poor. In response to the above problems, the main solutions currently include constructing an ordered nano-microphase separation structure, designing a cross-linked structure, designing and selecting alkali-resistant cationic groups and polymer backbones, and blending strategies. Researchers hope to obtain anion exchange membranes with high ionic conductivity, high dimensional stability, good mechanical properties and chemical stability through the above methods.

[0004] Studies have found that when polybenzimidazole is used as the main chain of anion exchange membrane, it has excellent thermal stability and chemical stability, and maintains structural stability and is not easy to degrade under high temperature or harsh chemical environment. In addition, polybenzimidazole has high mechanical strength and can withstand certain mechanical stress, ensuring the service life and application effect of the membrane. In addition, the main chain structure is highly designable, and ion exchange groups can be introduced through chemical modification to improve ion conductivity. CN117964932A discloses a polysulfone cross-linked polybenzimidazole interpenetrating network anion exchange membrane, which is obtained by chemical cross-linking to obtain an anion exchange membrane with higher ionic conductivity and good dimensional stability. Its structural formula is as follows:

[0005] .

[0006] CN108623806A discloses an anion exchange membrane of polybenzimidazole with side ammonium groups, which contains multiple ammonium structures on the side chains of the membrane, and this structure plays a vital role in improving ion conductivity. Its structural formula is as follows:

[0007] .

[0008] However, the existing technologies for chemical modification of polybenzimidazole currently focus on the grafting of a single cationic group and cross-linking with other polymer main chains, but this may lead to problems such as a high swelling rate or relatively low ionic conductivity.

[0009] Therefore, it is of great significance to study a cross-linked polybenzimidazole anion exchange membrane and a preparation method thereof to solve the problems existing in the prior art. Summary of the invention

[0010] The purpose of the present invention is to solve the problems existing in the prior art and provide a cross-linked polybenzimidazole anion exchange membrane and a preparation method thereof.

[0011] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0012] A cross-linked polybenzimidazole anion exchange membrane, wherein the cross-linked polybenzimidazole has a chemical structure as shown in Formula I or Formula II;

[0013] ;

[0014] Formula I

[0015] ;

[0016] Formula II

[0017] Wherein, R is the quaternary ammonium ion introduced in the cross-linking agent, which is , or , the wavy line indicates the position of the chemical bond connection; x=y=z=1 or x=y=z=2, in Formula I, m+n+i+j=1, 0.05%≤n+i+j≤0.15; in Formula II, m+n+i=1, 0.05≤n+i≤0.15; that is, the proportion of the cross-linking agent is controlled at 5%~15%, and the grafting rate of 2,3-epoxypropyltrimethylammonium chloride or long side chain piperidine quaternary ammonium salt is controlled at 85%~95%.

[0018] The reasons why the chemical modification of polybenzimidazole is concentrated on the grafting of a single cationic group leads to a higher swelling rate are as follows:

[0019] (1) After the cationic groups are grafted, the interaction between the molecular chains of polybenzimidazole changes. The originally tightly arranged molecular chains are stretched out due to the presence of the cationic groups, and the distance between the molecular chains increases, forming more gaps and free volumes. When exposed to water, water molecules can more easily enter these gaps, causing them to swell, and the swelling rate increases accordingly. (2) The grafting of cationic groups may destroy the crystalline structure of polybenzimidazole, reduce its crystallinity, increase the amorphous region, and make the molecular chains in the amorphous region looser, making it easier to absorb and accommodate water molecules, resulting in an increase in the swelling rate.

[0020] The cross-linking of polybenzimidazole with other polymer backbones results in relatively low ionic conductivity for the following reasons:

[0021] (1) The cross-linking reaction will cause polybenzimidazole to form a three-dimensional network structure with other polymers. Although this structure can improve the mechanical strength and stability of the membrane, it will also make the polymer network denser. When ions are transported in the membrane, they need to pass through these cross-linked channels. The dense network structure will increase the resistance to ion transport, making the movement of ions difficult, resulting in a decrease in ionic conductivity. (2) After cross-linking, the mobility of polymer segments is restricted. The conduction of ions in polymers is closely related to the movement of polymer segments. The restricted movement of segments will lead to a weakening of the synergistic effect of ion migration. (3) When polybenzimidazole is cross-linked with other polymer main chains, if the two polymers are not compatible, phase separation is likely to occur. Even in the case of good compatibility, there may be microscopic inhomogeneities. This inhomogeneity will cause the ion transport channel to be interrupted or discontinuous locally. Ions will encounter more obstacles during the transport process, which is not conducive to the smooth conduction of ions, thereby reducing ionic conductivity.

[0022] The cross-linked polybenzimidazole of the present invention is a structure in which a quaternary ammonium salt and a flexible dicationic crosslinking agent are grafted simultaneously. A large amount of quaternary ammonium salt is grafted in the structure to meet the requirement of high ion exchange capacity of the anion exchange membrane, thereby obtaining an anion exchange membrane with high ion conductivity. Generally speaking, the higher the ion exchange capacity of the membrane, the higher the ion conductivity. Among them, increasing the ion exchange capacity of the membrane is an efficient method to improve the ion conductivity, but with the increase of the ion exchange capacity, the swelling rate of the membrane increases, and the mechanical properties and dimensional stability of the membrane deteriorate. However, a small amount of flexible dicationic crosslinking agent is grafted in the structure of the present invention to construct a crosslinked network, which improves the ion exchange capacity of the membrane while ensuring good dimensional stability and mechanical properties of the membrane; and the crosslinking agent contains two quaternary ammonium cations, and the flexible chain of the crosslinking agent is relatively long, which will alleviate the disadvantages brought by crosslinking (for example, a dense network structure may cause greater resistance to ion movement).

[0023] As the preferred technical solution:

[0024] The cross-linked polybenzimidazole anion exchange membrane as described above has a water absorption rate of 45.2-54.5% at 80°C, a swelling rate of <15% at 80°C, an ion conductivity of 157.8-178.4 mS / cm at 80°C, a tensile strength of 54.6-55.9 MPa, and an elongation at break of 11.7-13.5%.

[0025] The present invention also provides a method for preparing a cross-linked polybenzimidazole anion exchange membrane as described above, firstly adding 2,3-epoxypropyltrimethylammonium chloride to a polybenzimidazole solution, and reacting at 80-100° C. for 12-48 hours; then adding a flexible dicationic crosslinking agent and NaH to the solution after the reaction (since 2,3-epoxypropyltrimethylammonium chloride reacts easily with polybenzimidazole and no additional Lewis base is required to promote the reaction, NaH is added when the crosslinking agent is added here), reacting at 80-100° C. for 12-48 hours, precipitating the reaction solution in ethyl acetate, filtering, washing with ethanol and drying to obtain a cross-linked polybenzimidazole, and finally dissolving the cross-linked polybenzimidazole to form a casting solution, and drying After the film is dried, it is soaked and washed with a KOH solution or a NaOH solution to obtain a cross-linked polybenzimidazole anion exchange membrane; or it is prepared by a "post-crosslinking" strategy, that is, first add 2,3-epoxypropyltrimethylammonium chloride to the polybenzimidazole solution, react at 80-100°C for 12-48h, precipitate the reaction solution in ethyl acetate, filter, wash with ethanol and dry to obtain a grafted polybenzimidazole, then dissolve the grafted polybenzimidazole to form a casting solution, dry it to form a film, place it in an ethanol solution of a flexible dicationic crosslinker and NaH, react at 80-100°C for 12-48h, and then soak and wash with a KOH solution or a NaOH solution to obtain a cross-linked polybenzimidazole anion exchange membrane. The "post-crosslinking" strategy in the present invention has a unique advantage in improving the solubility of the cross-linked product. In the initial stage, the grafted polybenzimidazole has relatively good solubility, which is conducive to its uniform dispersion and film formation. Afterwards, through the "post-crosslinking" strategy, the degree of crosslinking and the type and amount of crosslinking agent and other factors are precisely controlled, so that the anion exchange membrane has a good crosslinked network structure to ensure its excellent performance, while avoiding the problem of a sharp drop in solubility and difficulty in film formation caused by excessive crosslinking.

[0026] A small amount of NaH is added during the preparation to promote the reaction. NaH is a Lewis base. In the reaction system, it can deprotonate the -NH group of the imidazole ring in the main chain. When the -NH group loses a proton, a nitrogen anion is formed. The electron cloud density of this nitrogen anion is higher than that of the -NH group, and the nucleophilicity is greatly enhanced. The nucleophilicity of the original -NH group is limited to a certain extent due to the participation of electrons in the conjugated system, but after the formation of the nitrogen anion, it can more effectively attack the carbon atom in the alkyl bromide. In addition, since there are multiple reaction sites on the imidazole ring in the main chain, the addition of NaH can guide the reaction to proceed mainly at the -NH group. Since NaH deprotonates the -NH group, the reaction activity of this site is significantly enhanced, and it is easier to react with alkyl bromide than other sites, thereby improving the selectivity of the reaction to a certain extent, and a cross-linked polybenzimidazole-based anion exchange membrane is obtained based on this. This is different from the reactivity of polyaryl piperidines commonly used in current literature. Here, N-methyl piperidine usually reacts with alkyl bromide. The nitrogen atom in N-methyl piperidine has a pair of lone electrons, which makes it highly nucleophilic. As a nucleophilic reagent, it can easily attack the carbon cation connected to the bromine atom in the alkyl bromide. Therefore, this reaction to form quaternary ammonium salts can usually occur under relatively mild conditions.

[0027] The molar ratio of 2,3-epoxypropyltrimethylammonium chloride, polybenzimidazole, and flexible dicationic crosslinker is related to the ratio of grafting rate and crosslinking degree. The molar ratio of 2,3-epoxypropyltrimethylammonium chloride to polybenzimidazole is 2-3:1, the molar ratio of flexible dicationic crosslinker to polybenzimidazole is 1-3:10, and the molar ratio of NaH to flexible dicationic crosslinker is 1-3:1;

[0028] The present invention also provides a method for preparing the cross-linked polybenzimidazole anion exchange membrane as described above, firstly, adding a long side chain piperidine quaternary ammonium salt and NaH to a polybenzimidazole solution (because the long side chain piperidine quaternary ammonium salt is relatively difficult to react with the polybenzimidazole, a certain amount of Lewis base needs to be added to promote the reaction, so when the long side chain piperidine quaternary ammonium salt is added, a sufficient amount of NaH has been added, and when the cross-linking agent is added, no additional NaH needs to be added), reacting at 80-100° C. for 12-48 hours; then adding a flexible dicationic cross-linking agent to the solution after the reaction, reacting at 80-100° C. for 12-48 hours, precipitating the reaction solution in ethyl acetate, filtering, washing with ethanol and drying to obtain a cross-linked polybenzimidazole, and finally The polybenzimidazole anion exchange membrane is prepared by dissolving to form a casting solution, drying to form a film, and then soaking and washing with a KOH solution or a NaOH solution; or by a "post-crosslinking" strategy, that is, first adding a long side chain piperidine quaternary ammonium salt and NaH to the polybenzimidazole solution, reacting at 80-100°C for 12-48 hours, precipitating the reaction solution in ethyl acetate, filtering, washing with ethanol and drying to obtain a grafted polybenzimidazole, and then dissolving the grafted polybenzimidazole to form a casting solution, drying to form a film, placing it in an ethanol solution of a flexible dicationic crosslinker and NaH, reacting at 80-100°C for 12-48 hours, and then soaking and washing with a KOH solution or a NaOH solution to obtain a cross-linked polybenzimidazole anion exchange membrane.

[0029] The actual molar ratio of long side chain piperidine quaternary ammonium salt, polybenzimidazole, and flexible dicationic crosslinker is related to the ratio of grafting rate and crosslinking degree. The molar ratio of long side chain piperidine quaternary ammonium salt to polybenzimidazole is 2-3:1, the molar ratio of flexible dicationic crosslinker to polybenzimidazole is 1-3:10, and the molar ratio of NaH to polybenzimidazole is 2-3:1;

[0030] The synthesis method of the long side chain piperidine quaternary ammonium salt is as follows: 1,6-dibromohexane is dissolved in ethyl acetate, N-methylpiperidine is added dropwise at a rate of 0.05 mL per 2 seconds under stirring at room temperature, and then the mixture is reacted at 30-50° C. for 36-72 hours, and then the white precipitate in the reaction solution is filtered, washed and dried to obtain the long side chain piperidine quaternary ammonium salt;

[0031] The molar ratio of 1,6-dibromohexane to N-methylpiperidine is 2-4:1, and the concentration of the solution obtained by dissolving 1,6-dibromohexane in ethyl acetate is 1.0-2.0 mol / L.

[0032] The flexible dicationic crosslinker is DBH-1, DBH-2, DPy-1, DPy-2, DPip-1 or DPip-2;

[0033] The chemical formulas of DBH-1, DBH-2, DPy-1, DPy-2, DPip-1 and DPip-2 are as follows:

[0034] ;

[0035] ;

[0036] ;

[0037] ;

[0038] ;

[0039] ;

[0040] The synthesis method of DBH-1 or DBH-2 is as follows: dissolving dibromide A in acetonitrile to obtain a dibromide A solution, dissolving tetramethyldiamine in acetonitrile to obtain a tetramethyldiamine solution, adding the tetramethyldiamine solution to the dibromide A solution, reacting at 60-80° C. for 12-36 hours, filtering the reaction solution and collecting the filtrate, then drying the filtrate using a rotary evaporator to obtain a white powder, washing with ether and drying to obtain a flexible dicationic crosslinking agent DBH-1 or DBH-2;

[0041] Dibromide A is 1,5-dibromopentane or 1,6-dibromohexane;

[0042] Tetramethyldiamine is N,N,N,N-tetramethyl-1,6-hexanediamine or N1,N1,N8,N8-tetramethyloctane-1,8-diamine;

[0043] The molar ratio of dibromide A to tetramethyldiamine is 5-10:1, the concentration of dibromide A solution is 0.5-0.7 mol / L, and the concentration of tetramethyldiamine solution is 0.2-0.3 mol / L;

[0044] The synthesis method of DPy-1, DPy-2, DPip-1 or DPip-2 is as follows: dissolving tetrahydropyrrole and K2CO3, or piperidine and K2CO3 in ethanol, heating to 60-90°C and stirring, then adding an ethanol solution of dibromide B to the obtained solution, and continuing to stir and react for 48-72 hours, then pouring the obtained reaction solution into deionized water, extracting with ethyl acetate 2-4 times, then drying with Na2SO4 and filtering, collecting the organic phase and rotary evaporating with a rotary evaporator to obtain a yellow liquid, dissolving the yellow liquid and 1,5-dibromopentane or 1,6-dibromohexane in an amount of 2-4 times the mole of the yellow liquid in acetonitrile, stirring at 60-90°C for 24-48 hours, precipitating with ether after the reaction to obtain a white solid, washing with ether 2-4 times, and vacuum drying for 24-48 hours to obtain a flexible dicationic crosslinker DPy-1, DPy-2, DPip-1 or DPip-2;

[0045] Dibromide B is 1,6-dibromohexane or 1,8-dibromooctane;

[0046] The molar ratio of tetrahydropyrrole or piperidine to dibromide B is 2-4:1, and the molar ratio of K2CO3 to tetrahydropyrrole is 1-2:1; in the solution obtained by dissolving tetrahydropyrrole and K2CO3, or piperidine and K2CO3 in ethanol, the concentration of tetrahydropyrrole or piperidine is 1.0-2.0 mol / L; the concentration of the ethanol solution of dibromide B is 0.5-1.0 mol / L.

[0047] As the preferred technical solution:

[0048] In the method for preparing a cross-linked polybenzimidazole anion exchange membrane as described above, the polybenzimidazole solution is obtained by adding polybenzimidazole to dimethyl sulfoxide and then dissolving the polybenzimidazole at 60-80°C.

[0049] In the method for preparing a cross-linked polybenzimidazole anion exchange membrane as described above, the concentration of the polybenzimidazole solution is 2-5wt%.

[0050] In the method for preparing a cross-linked polybenzimidazole anion exchange membrane as described above, the casting solution is obtained by dissolving the cross-linked polybenzimidazole in dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, and the concentration of the casting solution is 2-5wt%.

[0051] In the method for preparing a cross-linked polybenzimidazole anion exchange membrane as described above, the drying temperature is 60-100°C.

[0052] Beneficial effects:

[0053] (1) A method for preparing a cross-linked polybenzimidazole anion exchange membrane of the present invention simultaneously grafts a cationic group and a flexible dicationic crosslinking agent onto polybenzimidazole, thereby achieving a balance between the ionic conductivity and the swelling rate of the anion exchange membrane and having good mechanical properties; in addition, the tight network structure formed by cross-linking can hinder OH - The excessive permeation and damage to the membrane structure, that is, the chemical stability of AEM is improved; in addition, the cationic groups selected contain hydrophilic -OH groups or longer alkyl side chains, which is beneficial to the OH groups of AEM. - Transport is also favorable, ultimately resulting in the AEM having high ionic conductivity and mechanical properties under a certain dimensional stability (swelling ratio <15%).

[0054] (2) The cross-linked polybenzimidazole anion exchange membrane of the present invention has high ionic conductivity, high dimensional stability, good mechanical properties and chemical stability, and has potential application prospects in anion exchange membrane water electrolysis and fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of the cross-linked polybenzimidazole of Example 1;

[0056] Figure 2 This is the infrared spectrum of the cross-linked polybenzimidazole of Example 1. DETAILED DESCRIPTION

[0057] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0058] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:

[0059] Ionic conductivity at 80°C: The membrane sample (1 cm×4 cm) was measured by the four-electrode method at 80°C (heated in deionized water) using a Solartron analytical 1470E electrochemical workstation. The test frequency was 0.1 Hz~100 kHz. The ionic conductivity (σ, S / cm) can be calculated using the following formula:

[0060] ;

[0061] Where, L (cm) is the distance between two adjacent electrodes, S (cm 2) is the cross-sectional area of ​​the film sample, and R (Ω) is the impedance.

[0062] Water absorption and swelling rate at 80℃: Soak the membrane sample (2 cm×3 cm) in deionized water at 80℃ for 48h, take out the membrane sample, use filter paper to absorb the water on the membrane surface, weigh it immediately (m1) and measure the length of the membrane sample (L1); after the test, dry the wet membrane sample to constant weight, and test its dry weight (m2) and length (L2). The water absorption (WU) and swelling rate (SR) of the membrane are calculated by the following formula:

[0063] ;

[0064] .

[0065] Tensile strength and elongation at break: The mechanical properties of the anion exchange membrane were tested using an Instron universal tensile testing machine; the membrane samples were cut into dumbbell shapes and the tensile rate was 5 mm / min.

[0066] Example 1

[0067] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0068] (1) Synthesis of DBH-1;

[0069] 1,5-dibromopentane was dissolved in acetonitrile to obtain a 1,5-dibromopentane solution with a concentration of 0.5 mol / L. N,N,N,N-tetramethyl-1,6-hexanediamine was dissolved in acetonitrile to obtain a N,N,N,N-tetramethyl-1,6-hexanediamine solution with a concentration of 0.2 mol / L. The N,N,N,N-tetramethyl-1,6-hexanediamine solution was added dropwise to the 1,5-dibromopentane solution at a rate of 0.05 mL per second, and the mixture was reacted at 60° C. for 24 hours. The reaction solution was then filtered and the filtrate was collected. The filtrate was then dried using a rotary evaporator to obtain a white powder. The flexible dicationic crosslinker DBH-1 was obtained after washing with ether and drying. The chemical formula of DBH-1 is as follows:

[0070] ;

[0071] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 2.5 wt %;

[0072] (3) First, 2,3-epoxypropyltrimethylammonium chloride (GTA) was added to the polybenzimidazole solution and reacted at 80°C for 24 hours; then, a flexible dicationic crosslinker and NaH were added to the reacted solution and reacted at 80°C for 24 hours. The reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain a cross-linked polybenzimidazole. Finally, the cross-linked polybenzimidazole was dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2 wt%. After drying at 80°C to form a membrane, the membrane was immersed in a 1 M KOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-QA-DBH-1.

[0073] The molar ratio of 2,3-epoxypropyltrimethylammonium chloride to polybenzimidazole is 2:1, the molar ratio of polybenzimidazole to the flexible dicationic crosslinker is 10:3, and the molar ratio of NaH to the flexible dicationic crosslinker is 3:1.

[0074] The finally prepared cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 45.2% at 80°C, a swelling rate of 11.5% at 80°C, an ion conductivity of 157.8 mS / cm at 80°C, a tensile strength of 55.6 MPa, and an elongation at break of 11.7%; the cross-linked polybenzimidazole has the following chemical structure:

[0075] ;

[0076] Among them, x = y = z= 1, m+n+i+j=1, n+i+j =0.15;

[0077] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 110500 g / mol‌.

[0078] like Figure 1 In the H NMR spectrum shown, the characteristic peaks at chemical shifts of 6.18 ppm, 4.64 ppm, 4.39 ppm, 3.54 ppm and 3.19 ppm correspond to the hydroxyl group (6.18 ppm), methyl proton (4.64 ppm), methylene proton (4.39 ppm and 3.54 ppm) and methyl proton (3.19 ppm) of the side chain, which confirms that 2,3-epoxypropyltrimethylammonium chloride (GTA) is grafted on the PBI skeleton and a ring-opening reaction occurs; the chemical shift of 3.03 ppm corresponds to the methyl proton in the flexible dicationic crosslinker DBH-1, and the chemical shift of 1.23~1.86 ppm corresponds to the alkyl chain proton in DBH-1. Through the above analysis, it is confirmed that the cross-linked polybenzimidazole structure in Example 1 is synthesized.

[0079] like Figure 2The FT-IR spectrum of the prepared Example 1 shown provides further evidence that -1 and 2851 cm -1 Two obvious absorption peaks appeared at , which were attributed to the stretching vibration of methyl and methylene.

[0080] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-QA-DBH-1 are as follows: (1) The structure contains hydrophilic -OH groups, which increases the water absorption of AEM and forms more hydration channels, thereby improving ion conductivity; (2) The cross-linked structure forms a network structure inside the polymer, which not only effectively prevents AEM from excessive swelling due to water absorption, keeps the size of AEM relatively stable, but also improves the chemical stability of AEM. In addition, the appropriate cross-linked structure increases the tensile strength and toughness of AEM; (3) The cross-linking agent contains two quaternary ammonium groups, and the introduction of the cross-linking agent enables AEM to construct a well-ordered microphase separation structure, which helps to improve ion conductivity and reduce the problem of reduced ion transmission efficiency caused by the cross-linked structure.

[0081] Comparative Example 1

[0082] A method for preparing a grafted polybenzimidazole anion exchange membrane is basically the same as that of Example 1, except that step (1) is omitted, that is, a flexible dicationic crosslinking agent and NaH are not added in step (3).

[0083] The final grafted polybenzimidazole anion exchange membrane PBI-QA has a swelling rate of 30.6% at 80°C, an ion conductivity of 96.4 mS / cm at 80°C, and a tensile strength of 52.1 MPa; the grafted polybenzimidazole has the following chemical structure:

[0084] ;

[0085] Among them, e=0.85, f=0.15; e represents the proportion of the main chain containing grafted groups, and f represents the proportion of the main chain without grafted groups;

[0086] The viscosity average molecular weight M of grafted polybenzimidazole η = 102060 g / mol‌.

[0087] By comparing Comparative Example 1 with Example 1, it can be found that the swelling rate of Comparative Example 1 increases, and the ionic conductivity and tensile strength are reduced. This is because compared with Example 1, Comparative Example 1 lacks the effect of the flexible dicationic crosslinker. The introduction of the crosslinker in Example 1 forms a network structure inside it, and the tensile strength of the membrane is larger and the swelling rate is smaller. In addition, the crosslinker in Example 1 contains two quaternary ammonium ions, and the crosslinker has flexible long side chains, so that a well-ordered microphase separation structure is formed in the structure, and the ionic conductivity is further increased.

[0088] Comparative Example 2

[0089] A method for preparing a cross-linked polybenzimidazole anion exchange membrane is basically the same as that in Example 1, except that: in step (3), 2,3-epoxypropyltrimethylammonium chloride (GTA) is not added for reaction.

[0090] The finally prepared cross-linked polybenzimidazole anion exchange membrane PBI-DBH-1 has an ion conductivity of 56.7 mS / cm at 80°C and an elongation at break of 9.5%. The cross-linked polybenzimidazole has the following chemical structure:

[0091] ;

[0092] Among them, a=0.85, b+c=0.15; a represents the proportion of the main chain without cross-linking agent, and b+c represents the proportion of the main chain with cross-linking agent;

[0093] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 101206 g / mol‌.

[0094] By comparing Comparative Example 2 with Example 1, it can be found that the ionic conductivity and elongation at break of Comparative Example 2 are smaller. This is because there is only a cross-linked structure in Comparative Example 2 without grafting, so the number of quaternary ammonium ions is small, the ion exchange capacity is low, and therefore the ionic conductivity is small; since the flexibility of the membrane of Comparative Example 2 and the mobility of the polymer chain segments are reduced, that is, the elongation at break is reduced.

[0095] Example 2

[0096] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0097] (1) Synthesis of DBH-1;

[0098] 1,5-dibromopentane was dissolved in acetonitrile to obtain a 1,5-dibromopentane solution with a concentration of 0.7 mol / L. N,N,N,N-tetramethyl-1,6-hexanediamine was dissolved in acetonitrile to obtain a N,N,N,N-tetramethyl-1,6-hexanediamine solution with a concentration of 0.3 mol / L. The N,N,N,N-tetramethyl-1,6-hexanediamine solution was added dropwise to the 1,5-dibromopentane solution at a rate of 0.05 mL per second, and the mixture was reacted at 80° C. for 12 h. The reaction solution was then filtered and the filtrate was collected. The filtrate was then dried using a rotary evaporator to obtain a white powder. The flexible dicationic crosslinker DBH-1 was obtained after washing with ether and drying. The chemical formula of DBH-1 is as follows:

[0099] ;

[0100] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 5 wt %;

[0101] (3) Dissolve 1,6-dibromohexane in ethyl acetate, add N-methylpiperidine dropwise at a rate of 0.05 mL per 2 seconds under stirring at room temperature, and then react at 40°C for 48 hours. Then, filter, wash and dry the white precipitate in the reaction solution to obtain a long side chain piperidine quaternary ammonium salt 6Br-Pip;

[0102] The molar ratio of 1,6-dibromohexane to N-methylpiperidine is 2:1, and the concentration of the solution obtained by dissolving 1,6-dibromohexane in ethyl acetate is 1.0 mol / L;

[0103] (4) First, long side chain piperidine quaternary ammonium salt and NaH were added to the polybenzimidazole solution and reacted at 80°C for 24 hours. Then, a flexible dicationic crosslinker was added to the solution after the reaction and reacted at 80°C for 24 hours. The reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain a cross-linked polybenzimidazole. Finally, the cross-linked polybenzimidazole was dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2wt%. After drying at 80°C to form a membrane, it was immersed in 1M KOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip-DBH-1.

[0104] The molar ratio of the long side chain piperidine quaternary ammonium salt to the polybenzimidazole is 2:1, the molar ratio of the polybenzimidazole to the flexible dicationic crosslinker is 10:3, and the molar ratio of NaH to the polybenzimidazole is 3:1.

[0105] The finally prepared cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 51.3% at 80°C, a swelling rate of 12.6% at 80°C, an ion conductivity of 172.4 mS / cm at 80°C, a tensile strength of 55.9 MPa, and an elongation at break of 12.2%; the cross-linked polybenzimidazole has the following chemical structure:

[0106] ;

[0107] Among them, x = y = z= 1, m+n+i=1, n+i=0.15;

[0108] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 115030 g / mol‌.

[0109] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip-DBH-1 are as follows: (1) The long side chain piperidine cationic groups and the cross-linking agent containing two quaternary ammonium groups introduced into AEM both help to construct an ordered microphase separation structure, thereby improving the ionic conductivity; (2) The cross-linked structure enables a network structure to be formed inside the polymer, thereby improving the dimensional stability, mechanical properties, and chemical stability of AEM.

[0110] Comparative Example 3

[0111] A method for preparing a grafted polybenzimidazole anion exchange membrane is basically the same as that of Example 2, except that step (1) is omitted, that is, a flexible dicationic crosslinking agent is not added in step (4).

[0112] The final grafted polybenzimidazole anion exchange membrane PBI-6Br-Pip has a swelling rate of 35.7% at 80°C, an ion conductivity of 102.7 mS / cm at 80°C, and a tensile strength of 54.4 MPa; the grafted polybenzimidazole has the following chemical structure:

[0113] ;

[0114] Among them, e=0.85, f=0.15; e represents the proportion of the main chain containing grafted groups, and f represents the proportion of the main chain without grafted groups;

[0115] The viscosity average molecular weight M of grafted polybenzimidazole η = 102500 g / mol‌.

[0116] By comparing Comparative Example 3 with Example 2, it can be found that the swelling rate of Comparative Example 3 increases, and the ionic conductivity and tensile strength are reduced. This is because compared with Example 2, Comparative Example 3 lacks the effect of the flexible dicationic crosslinker. In Example 2, the introduction of the crosslinker forms a network structure inside it, and the tensile strength of the membrane is larger and the swelling rate is reduced. In addition, the crosslinker contains two quaternary ammonium ions and has flexible long side chains, so that a well-ordered microphase separation structure is formed in the structure, and the ionic conductivity is further increased.

[0117] Example 3

[0118] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0119] (1) Synthesis of DBH-2;

[0120] 1,6-dibromohexane was dissolved in acetonitrile to obtain a 1,6-dibromohexane solution with a concentration of 0.5 mol / L. N1,N1,N8,N8-tetramethyloctane-1,8-diamine was dissolved in acetonitrile to obtain a N1,N1,N8,N8-tetramethyloctane-1,8-diamine solution with a concentration of 0.2 mol / L. The N1,N1,N8,N8-tetramethyloctane-1,8-diamine solution was added dropwise to the 1,6-dibromohexane solution at a rate of 0.05 mL per second, and the mixture was reacted at 60° C. for 24 hours. The reaction solution was then filtered and the filtrate was collected. The filtrate was then dried using a rotary evaporator to obtain a white powder. The flexible dicationic crosslinker DBH-2 was obtained after washing with ether and drying. The chemical formula of DBH-2 is as follows:

[0121] ;

[0122] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 2.5 wt %;

[0123] (3) Preparation by the "post-crosslinking" strategy: first, 2,3-epoxypropyltrimethylammonium chloride (GTA) was added to the polybenzimidazole solution, and the reaction was carried out at 80°C for 24 hours. The reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain a grafted polybenzimidazole. The grafted polybenzimidazole was then dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2wt%, which was dried at 80°C to form a film. After that, it was placed in an ethanol solution of a flexible dicationic crosslinker and NaH, reacted at 80°C for 48 hours, and then immersed in a 1M NaOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-QA-DBH-2.

[0124] The molar ratio of 2,3-epoxypropyltrimethylammonium chloride to polybenzimidazole is 3:1, the molar ratio of polybenzimidazole to the flexible dicationic crosslinker is 10:1, and the molar ratio of NaH to the flexible dicationic crosslinker is 1:1.

[0125] The finally prepared cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 45.7% at 80°C, a swelling rate of 13.1% at 80°C, an ion conductivity of 158.6 mS / cm at 80°C, a tensile strength of 55.3 MPa, and an elongation at break of 11.9%; the cross-linked polybenzimidazole has the following chemical structure:

[0126] ;

[0127] Among them, x = y = z= 2, m+n+i+j=1, n+i+j =0.05;

[0128] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 107580 g / mol‌.

[0129] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-QA-DBH-2 are as follows: similar to the structural characteristics of PBI-QA-DBH-1; different from PBI-QA-DBH-1, the alkyl chain of the dicationic crosslinker of PBI-QA-DBH-2 is longer, so the free volume in AEM is relatively larger, the water absorption rate is relatively higher, and it is more conducive to ion migration, thereby improving ionic conductivity.

[0130] Example 4

[0131] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0132] (1) Synthesis of DBH-2;

[0133] 1,6-dibromohexane was dissolved in acetonitrile to obtain a 1,6-dibromohexane solution with a concentration of 0.7 mol / L, N1,N1,N8,N8-tetramethyloctane-1,8-diamine was dissolved in acetonitrile to obtain a N1,N1,N8,N8-tetramethyloctane-1,8-diamine solution with a concentration of 0.3 mol / L, and the N1,N1,N8,N8-tetramethyloctane-1,8-diamine solution was added dropwise to the 1,6-dibromohexane solution at a rate of 0.05 mL per second, and the reaction was carried out at 60° C. for 24 hours, and then the reaction solution was filtered and the filtrate was collected. The filtrate was then dried using a rotary evaporator to obtain a white powder, which was washed with ether and dried to obtain a flexible dicationic crosslinker DBH-2. The chemical formula of DBH-2 is as follows:

[0134] ;

[0135] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 5 wt %;

[0136] (3) Dissolve 1,6-dibromohexane in ethyl acetate, add N-methylpiperidine dropwise at a rate of 0.05 mL per 2 seconds under stirring at room temperature, and then react at 30°C for 72 hours. Then, filter, wash and dry the white precipitate in the reaction solution to obtain a long side chain piperidine quaternary ammonium salt 6Br-Pip;

[0137] The molar ratio of 1,6-dibromohexane to N-methylpiperidine is 2:1, and the concentration of the solution obtained by dissolving 1,6-dibromohexane in ethyl acetate is 2.0 mol / L;

[0138] (4) Preparation by the "post-crosslinking" strategy: first, long side chain piperidine quaternary ammonium salt and NaH were added to the polybenzimidazole solution and reacted at 80°C for 24 hours. The reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain grafted polybenzimidazole. The grafted polybenzimidazole was then dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2wt%, which was dried at 80°C to form a film. After that, it was placed in an ethanol solution of a flexible dicationic crosslinker and NaH and reacted at 80°C for 48 hours. It was then immersed in a 1M NaOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip-DBH-2.

[0139] The molar ratio of the long side chain piperidine quaternary ammonium salt to the polybenzimidazole is 3:1, the molar ratio of the polybenzimidazole to the flexible dicationic crosslinker is 10:1, and the molar ratio of NaH to the polybenzimidazole is 2:1.

[0140] The finally obtained cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 51.7% at 80°C, a swelling rate of 14.1% at 80°C, an ion conductivity of 174.9 mS / cm at 80°C, a tensile strength of 55.3 MPa, and an elongation at break of 12.7%; the cross-linked polybenzimidazole has the following chemical structure:

[0141] ;

[0142] Among them, x = y = z= 2, m+n+i=1, n+i=0.05;

[0143] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 113070 g / mol‌.

[0144] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip-DBH-2 are as follows: Similar to the structural characteristics of PBI-6Br-Pip-DBH-1, the difference from PBI-6Br-Pip-DBH-1 is that the alkyl chain of the dicationic crosslinker of PBI-6Br-Pip-DBH-2 is longer, so the free volume in AEM is larger, the water absorption rate is relatively higher, and it is more conducive to ion migration, thereby improving ionic conductivity.

[0145] Example 5

[0146] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0147] (1) Synthesis of DPy-1;

[0148] Tetrahydropyrrole and K2CO3 were dissolved in ethanol, heated to 70°C and stirred, then, an ethanol solution of 1,6-dibromohexane was added to the resulting solution, and the reaction was continued to stir for 48 hours, then the resulting reaction solution was poured into deionized water, extracted with ethyl acetate three times, then dried with Na2SO4 and filtered, the organic phase was collected and rotary evaporated with a rotary evaporator to obtain a yellow liquid, the yellow liquid and 1,5-dibromopentane in an amount of 2 times the mole of the yellow liquid were dissolved in 30 mL of acetonitrile, stirred at 60°C for 24 hours, and precipitated with ether after the reaction to obtain a white solid, which was then washed with ether three times and vacuum dried for 48 hours to obtain a flexible dicationic crosslinker DPy-1, the chemical formula of DPy-1 is as follows;

[0149] ;

[0150] The molar ratio of tetrahydropyrrole to 1,6-dibromohexane is 2:1, and the molar ratio of K2CO3 to tetrahydropyrrole is 1.5:1; tetrahydropyrrole and K2CO3 are dissolved in ethanol to obtain a solution, and the concentration of tetrahydropyrrole is 1.0 mol / L; the concentration of the ethanol solution of 1,6-dibromohexane is 0.5 mol / L;

[0151] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 2.5 wt %;

[0152] (3) First, 2,3-epoxypropyltrimethylammonium chloride (GTA) was added to the polybenzimidazole solution and reacted at 80°C for 24 hours; then, a flexible dicationic crosslinker and NaH were added to the reacted solution and reacted at 80°C for 24 hours. The reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain a cross-linked polybenzimidazole; finally, the cross-linked polybenzimidazole was dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2 wt%, dried at 80°C to form a film, then immersed in a 1 M KOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-QA-DPy-1;

[0153] The molar ratio of 2,3-epoxypropyltrimethylammonium chloride to polybenzimidazole is 2:1, the molar ratio of polybenzimidazole to the flexible dicationic crosslinker is 10:3, and the molar ratio of NaH to the flexible dicationic crosslinker is 3:1.

[0154] The finally prepared cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 45.4% at 80°C, a swelling rate of 12.6% at 80°C, an ion conductivity of 159.1 mS / cm at 80°C, a tensile strength of 55.2 MPa, and an elongation at break of 11.9%; the cross-linked polybenzimidazole has the following chemical structure:

[0155] ;

[0156] Among them, x = y = z= 1, m+n+i+j=1, n+i+j=0.15;

[0157] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 112090 g / mol‌.

[0158] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-QA-DPy-1 are as follows: (1) The cationic group is a pyrrolyl quaternary ammonium ion, which increases the OH - The attack on the steric hindrance of the cationic group, that is, the chemical stability of the cationic group will be improved; (2) since the pyrrole ring replaces the quaternary ammonium salt, the free volume in the AEM is increased, and the water absorption rate of the AEM will be increased.

[0159] Comparative Example 4

[0160] A method for preparing a cross-linked polybenzimidazole anion exchange membrane is basically the same as that of Example 5, except that step (1) is omitted, that is, 2,3-epoxypropyltrimethylammonium chloride (GTA) is not added in step (3) for reaction.

[0161] The finally prepared cross-linked polybenzimidazole anion exchange membrane PBI-DPy-1 has an ion conductivity of 57.4 mS / cm at 80°C and an elongation at break of 10.2%. The cross-linked polybenzimidazole has the following chemical structure:

[0162] ; Among them, a=0.85, b+c=0.15; a represents the proportion of the main chain without cross-linking agent, and (b+c) represents the proportion of the main chain containing cross-linking agent.

[0163] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 103010 g / mol‌.

[0164] By comparing Comparative Example 4 and Example 5, it can be found that the ionic conductivity and elongation at break of Comparative Example 4 are smaller. This is because there is only a cross-linked structure in Comparative Example 4 without grafting, so the number of quaternary ammonium ions is small, the ion exchange capacity is low, and therefore the ionic conductivity is small; since the flexibility of the membrane of Comparative Example 4 and the mobility of the polymer chain segments are reduced, that is, the elongation at break is reduced.

[0165] Example 6

[0166] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0167] (1) Synthesis of DPy-1;

[0168] Tetrahydropyrrole and K2CO3 were dissolved in ethanol, heated to 70°C and stirred, then, an ethanol solution of 1,6-dibromohexane was added to the resulting solution, and the reaction was continued to stir for 48 hours, then the resulting reaction solution was poured into deionized water, extracted with ethyl acetate three times, then dried with Na2SO4 and filtered, the organic phase was collected and rotary evaporated with a rotary evaporator to obtain a yellow liquid, the yellow liquid and 1,5-dibromopentane in an amount of 4 times the mole of the yellow liquid were dissolved in 30 mL of acetonitrile, stirred at 60°C for 24 hours, and precipitated with ether after the reaction to obtain a white solid, which was then washed with ether three times and vacuum dried for 48 hours to obtain a flexible dicationic crosslinker DPy-1, the chemical formula of DPy-1 is as follows:

[0169] ;

[0170] The molar ratio of tetrahydropyrrole to 1,6-dibromohexane is 2:1, and the molar ratio of K2CO3 to tetrahydropyrrole is 1.5:1; tetrahydropyrrole and K2CO3 are dissolved in ethanol to obtain a solution, and the concentration of tetrahydropyrrole is 2.0 mol / L; the concentration of the ethanol solution of 1,6-dibromohexane is 1.0 mol / L;

[0171] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 5 wt %;

[0172] (3) Dissolve 1,6-dibromohexane in ethyl acetate, add N-methylpiperidine dropwise at a rate of 0.05 mL per 2 seconds under stirring at room temperature, and then react at 50°C for 36 hours. Then, filter, wash and dry the white precipitate in the reaction solution to obtain a long side chain piperidine quaternary ammonium salt 6Br-Pip;

[0173] The molar ratio of 1,6-dibromohexane to N-methylpiperidine is 2:1, and the concentration of the solution obtained by dissolving 1,6-dibromohexane in ethyl acetate is 1.5 mol / L;

[0174] (4) First, long side chain piperidine quaternary ammonium salt and NaH were added to the polybenzimidazole solution and reacted at 80°C for 24 hours; then, a flexible dicationic crosslinker was added to the solution after the reaction and reacted at 80°C for 24 hours, and the reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain a cross-linked polybenzimidazole; finally, the cross-linked polybenzimidazole was dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2wt%, dried at 80°C to form a membrane, and then immersed in a 1M KOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip-DPy-1;

[0175] The molar ratio of the long side chain piperidine quaternary ammonium salt to the polybenzimidazole is 2:1, the molar ratio of the polybenzimidazole to the flexible dicationic crosslinker is 10:3, and the molar ratio of NaH to the polybenzimidazole is 3:1.

[0176] The finally prepared cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 52.8% at 80°C, a swelling rate of 13.3% at 80°C, an ion conductivity of 175.3 mS / cm at 80°C, a tensile strength of 55.1 MPa, and an elongation at break of 12.9%; the cross-linked polybenzimidazole has the following chemical structure:

[0177] ;

[0178] Among them, x = y = z= 1, m+n+i=1, n+i=0.15;

[0179] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 118500 g / mol‌.

[0180] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip-DPy-1 are as follows: Similar to the structural characteristics of PBI-QA-DPy-1, the difference from PBI-QA-DPy-1 is that the long side chain piperidine quaternary ammonium salt in PBI-6Br-Pip-DPy-1 will form an obvious microphase separation structure, promote ion migration, and benefit the improvement of ion conductivity.

[0181] Example 7

[0182] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0183] (1) Synthesis of DPy-2;

[0184] Dissolve tetrahydropyrrole and K2CO3 in ethanol, heat to 70°C and stir, then add 1,8-dibromooctane ethanol solution to the resulting solution, continue stirring and reacting for 48 hours, then pour the resulting reaction solution into deionized water, extract with ethyl acetate three times, then dry with Na2SO4 and filter, collect the organic phase and use a rotary evaporator to evaporate to obtain a yellow liquid, dissolve the yellow liquid and 1,6-dibromohexane in an amount of 2 times the mole of the yellow liquid in acetonitrile, stir at 60°C for 24 hours, precipitate with ether after the reaction to obtain a white solid, wash with ether three times, and vacuum dry for 48 hours to obtain a flexible dicationic crosslinker DPy-2;

[0185] The molar ratio of tetrahydropyrrole to 1,8-dibromooctane is 2:1, and the molar ratio of K2CO3 to tetrahydropyrrole is 1.5:1; tetrahydropyrrole and K2CO3 are dissolved in ethanol to obtain a solution, and the concentration of tetrahydropyrrole is 1.0 mol / L; the concentration of the ethanol solution of 1,8-dibromooctane is 0.5 mol / L;

[0186] ;

[0187] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 2.5 wt %;

[0188] (3) Prepared by the "post-crosslinking" strategy, first add 2,3-epoxypropyltrimethylammonium chloride (GTA) to the polybenzimidazole solution, react at 80°C for 24 hours, then precipitate the reaction solution in ethyl acetate, filter, wash with ethanol and dry to obtain grafted polybenzimidazole; then dissolve the grafted polybenzimidazole in dimethyl sulfoxide to obtain a casting solution with a concentration of 2wt%, and dry it at 80°C to form a film; then place it in an ethanol solution of a flexible dicationic crosslinker and NaH, react at 80°C for 48 hours; then soak it in 1M NaOH solution and wash it with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-QA-DPy-2;

[0189] The molar ratio of 2,3-epoxypropyltrimethylammonium chloride to polybenzimidazole is 3:1, the molar ratio of polybenzimidazole to the flexible dicationic crosslinker is 10:1, and the molar ratio of NaH to the flexible dicationic crosslinker is 1:1.

[0190] The finally prepared cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 45.6% at 80°C, a swelling rate of 13.9% at 80°C, an ion conductivity of 160.4 mS / cm at 80°C, a tensile strength of 54.9 MPa, and an elongation at break of 12.2%; the cross-linked polybenzimidazole has the following chemical structure:

[0191] ;

[0192] Among them, x = y = z= 2, m+n+i+j=1, n+i+j=0.05;

[0193] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 111280 g / mol‌.

[0194] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-QA-DPy-2 are as follows: Similar to the structural characteristics of PBI-QA-DPy-1, the difference from PBI-QA-DPy-1 is that the alkyl chain of the dicationic crosslinker of PBI-QA-DPy-2 is longer, so the free volume in AEM is relatively larger, the water absorption rate is relatively higher, and it is more conducive to ion migration, thereby improving ionic conductivity.

[0195] Example 8

[0196] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0197] (1) Synthesis of DPy-2;

[0198] Tetrahydropyrrole and K2CO3 were dissolved in ethanol, heated to 70°C and stirred, then, an ethanol solution of 1,8-dibromooctane was added to the obtained solution, and the reaction was continued to stir for 48 hours, then the obtained reaction solution was poured into deionized water, extracted with ethyl acetate for 3 times, then dried with Na2SO4 and filtered, the organic phase was collected and rotary evaporated with a rotary evaporator to obtain a yellow liquid, the yellow liquid and 1,6-dibromohexane with a molar amount of 3 times relative to the yellow liquid were dissolved in acetonitrile, stirred at 60°C for 24 hours, and precipitated with ether after the reaction was completed to obtain a white solid, which was then washed with ether for 3 times and vacuum dried for 48 hours to obtain a flexible dicationic crosslinker DPy-2, the chemical formula of DPy-2 is as follows:

[0199] ;

[0200] The molar ratio of tetrahydropyrrole to 1,8-dibromooctane is 2:1, and the molar ratio of K2CO3 to tetrahydropyrrole is 1.5:1; the concentration of tetrahydropyrrole in the solution obtained by dissolving tetrahydropyrrole and K2CO3 in ethanol is 1.5 mol / L; the concentration of 1,8-dibromooctane in ethanol is 0.7 mol / L;

[0201] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 5 wt %;

[0202] (3) Dissolve 1,6-dibromohexane in ethyl acetate, add N-methylpiperidine dropwise at a rate of 0.05 mL per 2 seconds under stirring at room temperature, and then react at 30°C for 72 hours. Then, filter, wash and dry the white precipitate in the reaction solution to obtain a long side chain piperidine quaternary ammonium salt 6Br-Pip;

[0203] The molar ratio of 1,6-dibromohexane to N-methylpiperidine is 2:1, and the concentration of the solution obtained by dissolving 1,6-dibromohexane in ethyl acetate is 1.5 mol / L;

[0204] (4) Preparation by the "post-crosslinking" strategy: first, long side chain piperidine quaternary ammonium salt and NaH were added to the polybenzimidazole solution and reacted at 80°C for 24 hours. The reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain grafted polybenzimidazole. The grafted polybenzimidazole was then dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2wt%, which was dried at 80°C to form a membrane. After that, it was placed in an ethanol solution of a flexible dicationic crosslinker and NaH and reacted at 80°C for 48 hours. It was then soaked in 1M NaOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip-DPy-2.

[0205] The molar ratio of the long side chain piperidine quaternary ammonium salt to the polybenzimidazole is 3:1, the molar ratio of the polybenzimidazole to the flexible dicationic crosslinker is 10:1, and the molar ratio of NaH to the polybenzimidazole is 2:1.

[0206] The finally prepared cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 53.2% at 80°C, a swelling rate of 14.7% at 80°C, an ion conductivity of 176.7 mS / cm at 80°C, a tensile strength of 54.7 MPa, and an elongation at break of 13.3%; the cross-linked polybenzimidazole has the following chemical structure:

[0207] ;

[0208] Among them, x = y = z= 2, m+n+i=1, n+i=0.05;

[0209] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 116206 g / mol‌.

[0210] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip-DPy-2 are as follows: Similar to the structural characteristics of PBI-6Br-Pip-DPy-1. Unlike PBI-6Br-Pip-DPy-1, the alkyl chain of the dicationic crosslinker in PBI-6Br-Pip-DPy-2 is longer, so the free volume in AEM is relatively larger, the water absorption rate is relatively higher, and it is more conducive to ion migration, thereby improving ion conductivity.

[0211] Example 9

[0212] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0213] (1) Synthesis of DPip-1;

[0214] Piperidine and K2CO3 were dissolved in ethanol, heated to 70°C and stirred, then 1,6-dibromohexane ethanol solution was added to the obtained solution, and the reaction was continued with stirring for 48 hours, then the obtained reaction solution was poured into deionized water, extracted with ethyl acetate three times, then dried with Na2SO4 and filtered, the organic phase was collected and rotary evaporated with a rotary evaporator to obtain a yellow liquid, the yellow liquid and 1,5-dibromopentane with a molar amount of 2 times relative to the yellow liquid were dissolved in 30 mL of acetonitrile, stirred at 60°C for 24 hours, and precipitated with ether after the reaction to obtain a white solid, which was then washed with ether three times and vacuum dried for 48 hours to obtain a flexible dicationic crosslinker DPip-1. The chemical formula of DPip-1 is as follows:

[0215] ;

[0216] The molar ratio of piperidine to 1, 6-dibromohexane is 2:1, and the molar ratio of K2CO3 to piperidine is 1.5:1; piperidine and K2CO3 are dissolved in ethanol to obtain a solution, and the concentration of piperidine is 1.0 mol / L; the concentration of the ethanol solution of 1, 6-dibromohexane is 0.5 mol / L;

[0217] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 2.5 wt %;

[0218] (3) First, 2,3-epoxypropyltrimethylammonium chloride (GTA) was added to the polybenzimidazole solution and reacted at 80°C for 24 hours; then, a flexible dicationic crosslinker and NaH were added to the reacted solution and reacted at 80°C for 24 hours. The reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain a cross-linked polybenzimidazole; finally, the cross-linked polybenzimidazole was dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2 wt%, dried at 80°C to form a membrane, then immersed in a 1 M KOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-QA-DPip-1;

[0219] The molar ratio of 2,3-epoxypropyltrimethylammonium chloride to polybenzimidazole is 2:1, the molar ratio of polybenzimidazole to the flexible dicationic crosslinker is 10:3, and the molar ratio of NaH to the flexible dicationic crosslinker is 3:1.

[0220] The finally prepared cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 45.6% at 80°C, a swelling rate of 13.1% at 80°C, an ion conductivity of 160.8 mS / cm at 80°C, a tensile strength of 54.9 MPa, and an elongation at break of 12.0%; the cross-linked polybenzimidazole has the following chemical structure:

[0221] ;

[0222] Among them, x = y = z= 1, m+n+i+j=1, n+i+j=0.15;

[0223] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 115090 g / mol‌.

[0224] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-QA-DPip-1 are as follows: (1) The cationic group is a piperidinyl quaternary ammonium ion, which increases the OH -The attack on the steric hindrance of the cationic group, that is, the chemical stability of the cationic group will be improved; (2) since the piperidine ring replaces the quaternary ammonium salt, the free volume in AEM is increased, and the water absorption rate of AEM will be increased.

[0225] Comparative Example 5

[0226] A method for preparing a cross-linked polybenzimidazole anion exchange membrane is basically the same as Example 9, except that: in step (3), 2,3-epoxypropyltrimethylammonium chloride (GTA) is not added for reaction.

[0227] The finally prepared cross-linked polybenzimidazole anion exchange membrane PBI-DPip-1 has an ion conductivity of 58.1 mS / cm at 80°C and an elongation at break of 10.7%; the cross-linked polybenzimidazole has the following chemical structure:

[0228] ;

[0229] Among them, a=0.85, b+c=0.15; a represents the proportion of the main chain without cross-linking agent, and b+c represents the proportion of the main chain with cross-linking agent;

[0230] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 103200 g / mol‌.

[0231] Comparing Comparative Example 5 with Example 9, it can be found that the ion conductivity and elongation at break of Comparative Example 5 are smaller. This is because there is only a cross-linked structure in Comparative Example 5 without grafting, so the number of quaternary ammonium ions is small, the ion exchange capacity is low, and therefore the ion conductivity is small; the flexibility of the membrane of Comparative Example 5 and the mobility of the polymer chain segments are reduced, that is, the elongation at break is reduced.

[0232] Example 10

[0233] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0234] (1) Synthesis of DPip-1;

[0235] Piperidine and K2CO3 were dissolved in ethanol, heated to 70°C and stirred, then 1,6-dibromohexane ethanol solution was added to the obtained solution, and the stirring reaction was continued for 48 hours, then the obtained reaction solution was poured into deionized water, extracted with ethyl acetate three times, then dried with Na2SO4 and filtered, the organic phase was collected and rotary evaporated with a rotary evaporator to obtain a yellow liquid, the yellow liquid and 1,5-dibromopentane with 4 times the mole of the yellow liquid were dissolved in 30mL of acetonitrile, stirred at 60°C for 24 hours, and precipitated with ether after the reaction to obtain a white solid, which was then washed with ether three times and vacuum dried for 48 hours to obtain a flexible dicationic crosslinker DPip-1. The chemical formula of DPip-1 is as follows:

[0236] ;

[0237] The molar ratio of piperidine to 1, 6-dibromohexane is 2:1, and the molar ratio of K2CO3 to piperidine is 1.5:1; piperidine and K2CO3 are dissolved in ethanol to obtain a solution, and the concentration of piperidine is 2.0 mol / L; the concentration of the ethanol solution of 1, 6-dibromohexane is 1.0 mol / L;

[0238] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 5 wt %;

[0239] (3) Dissolve 1,6-dibromohexane in ethyl acetate, add N-methylpiperidine dropwise at a rate of 0.05 mL per 2 seconds under stirring at room temperature, and then react at 30°C for 72 hours. Then, filter, wash and dry the white precipitate in the reaction solution to obtain a long side chain piperidine quaternary ammonium salt 6Br-Pip;

[0240] The molar ratio of 1,6-dibromohexane to N-methylpiperidine is 2:1, and the concentration of the solution obtained by dissolving 1,6-dibromohexane in ethyl acetate is 1.5 mol / L;

[0241] (4) First, long side chain piperidine quaternary ammonium salt and NaH were added to the polybenzimidazole solution and reacted at 80°C for 24 hours; then, a flexible dicationic crosslinker was added to the solution after the reaction and reacted at 80°C for 24 hours, and the reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain a cross-linked polybenzimidazole; finally, the cross-linked polybenzimidazole was dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2wt%, dried at 80°C to form a membrane, and then immersed in a 1M KOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip--DPip-1;

[0242] The molar ratio of the long side chain piperidine quaternary ammonium salt to the polybenzimidazole is 2:1, the molar ratio of the polybenzimidazole to the flexible dicationic crosslinker is 10:3, and the molar ratio of NaH to the polybenzimidazole is 3:1.

[0243] The finally obtained cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 54.1% at 80°C, a swelling rate of 13.4% at 80°C, an ion conductivity of 177.2 mS / cm at 80°C, a tensile strength of 55.0 MPa, and an elongation at break of 13.2%; the cross-linked polybenzimidazole has the following chemical structure:

[0244] ;

[0245] Among them, x = y = z= 1, m+n+i=1, n+i=0.15;

[0246] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 121008 g / mol‌.

[0247] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip-DPip-1 are as follows: Similar to the structural characteristics of PBI-QA-DPip-1. Unlike PBI-6Br-Pip-DPip-1, the long side chain piperidine quaternary ammonium salt in PBI-6Br-Pip-DPip-1 will form an obvious microphase separation structure, promote ion migration, and help improve ion conductivity.

[0248] Embodiment 11

[0249] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0250] (1) Synthesis of DPip-2;

[0251] Piperidine and K2CO3 were dissolved in ethanol, heated to 70°C and stirred, then 1,8-dibromooctane ethanol solution was added to the obtained solution, and the reaction was continued to stir for 48 hours, then the obtained reaction solution was poured into deionized water, extracted with ethyl acetate for 3 times, then dried with Na2SO4 and filtered, the organic phase was collected and rotary evaporated with a rotary evaporator to obtain a yellow liquid, the yellow liquid and 1,6-dibromohexane with a molar ratio of 2 times relative to the yellow liquid were dissolved in 30 mL of acetonitrile, stirred at 60°C for 24 hours, and precipitated with ether after the reaction was completed to obtain a white solid, which was then washed with ether for 3 times and vacuum dried for 48 hours to obtain a flexible dicationic crosslinker DPip-2. The chemical formula of DPip-2 is as follows:

[0252] ;

[0253] The molar ratio of piperidine to 1,8-dibromooctane is 2:1, and the molar ratio of K2CO3 to piperidine is 1.5:1; piperidine and K2CO3 are dissolved in ethanol to obtain a solution, the concentration of piperidine is 1.0 mol / L; the concentration of the ethanol solution of 1,8-dibromooctane is 0.5 mol / L;

[0254] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 2.5 wt %;

[0255] (3) Preparation by the "post-crosslinking" strategy: first, 2,3-epoxypropyltrimethylammonium chloride (GTA) was added to the polybenzimidazole solution, and the reaction was carried out at 80°C for 24 hours. The reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain a grafted polybenzimidazole; then the grafted polybenzimidazole was dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2wt%, which was dried at 80°C to form a film; then it was placed in an ethanol solution of a flexible dicationic crosslinker and NaH, and reacted at 80°C for 48 hours; then it was soaked in 1M NaOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-QA-DPip-2;

[0256] The molar ratio of 2,3-epoxypropyltrimethylammonium chloride to polybenzimidazole is 3:1, the molar ratio of polybenzimidazole to the flexible dicationic crosslinker is 10:1, and the molar ratio of NaH to the flexible dicationic crosslinker is 1:1.

[0257] The finally obtained cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 46.1% at 80°C, a swelling rate of 14.5% at 80°C, an ion conductivity of 162.8 mS / cm at 80°C, a tensile strength of 54.6 MPa, and an elongation at break of 12.4%; the cross-linked polybenzimidazole has the following chemical structure:

[0258] ;

[0259] Among them, x = y = z= 2, m+n+i+j=1, n+i+j=0.05;

[0260] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 113603 g / mol‌.

[0261] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-QA-DPip-2 are as follows: Similar to the structural characteristics of PBI-QA-DPip-1, the difference from PBI-QA-DPip-1 is that the alkyl chain of the dicationic crosslinker of PBI-QA-DPip-2 is longer, so the free volume in AEM is relatively larger, the water absorption rate is relatively higher, and it is more conducive to ion migration, thereby improving ionic conductivity.

[0262] Example 12

[0263] A method for preparing a cross-linked polybenzimidazole anion exchange membrane, the specific steps are as follows:

[0264] (1) Synthesis of DPip-2;

[0265] Piperidine and K2CO3 were dissolved in ethanol, heated to 70°C and stirred, then 1,8-dibromooctane ethanol solution was added to the obtained solution, and the reaction was continued to stir for 48 hours, then the obtained reaction solution was poured into deionized water, extracted with ethyl acetate for 3 times, then dried with Na2SO4 and filtered, the organic phase was collected and rotary evaporated with a rotary evaporator to obtain a yellow liquid, the yellow liquid and 1,6-dibromohexane with 4 times the mole of the yellow liquid were dissolved in 30 mL of acetonitrile, stirred at 60°C for 24 hours, and precipitated with ether after the reaction was completed to obtain a white solid, which was then washed with ether for 3 times and vacuum dried for 48 hours to obtain a flexible dicationic crosslinker DPip-2. The chemical formula of DPip-2 is as follows:

[0266] ;

[0267] The molar ratio of piperidine to 1,8-dibromooctane is 2:1, and the molar ratio of K2CO3 to piperidine is 1.5:1; piperidine and K2CO3 are dissolved in ethanol to obtain a solution, the concentration of piperidine is 2.0 mol / L; the concentration of the ethanol solution of 1,8-dibromooctane is 1.0 mol / L;

[0268] (2) adding polybenzimidazole to dimethyl sulfoxide, and then dissolving it at 80° C. to obtain a polybenzimidazole solution with a concentration of 5 wt %;

[0269] (3) Dissolve 1,6-dibromohexane in ethyl acetate, add N-methylpiperidine dropwise at a rate of 0.05 mL per 2 seconds under stirring at room temperature, and then react at 30°C for 72 hours. Then, filter, wash and dry the white precipitate in the reaction solution to obtain a long side chain piperidine quaternary ammonium salt 6Br-Pip;

[0270] The molar ratio of 1,6-dibromohexane to N-methylpiperidine is 2:1, and the concentration of the solution obtained by dissolving 1,6-dibromohexane in ethyl acetate is 2.0 mol / L;

[0271] (4) Preparation by the "post-crosslinking" strategy: first, long side chain piperidine quaternary ammonium salt and NaH were added to the polybenzimidazole solution and reacted at 80°C for 24 hours. The reaction solution was precipitated in ethyl acetate, filtered, washed with ethanol and dried to obtain grafted polybenzimidazole. The grafted polybenzimidazole was then dissolved in dimethyl sulfoxide to obtain a casting solution with a concentration of 2wt%, which was dried at 80°C to form a film. It was then placed in an ethanol solution of a flexible dicationic crosslinker and NaH and reacted at 80°C for 48 hours. It was then soaked in 1M NaOH solution and washed with deionized water to obtain a cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip--DPip-2.

[0272] The molar ratio of the long side chain piperidine quaternary ammonium salt to the polybenzimidazole is 3:1, the molar ratio of the polybenzimidazole to the flexible dicationic crosslinker is 10:1, and the molar ratio of NaH to the polybenzimidazole is 2:1.

[0273] The finally obtained cross-linked polybenzimidazole anion exchange membrane has a water absorption rate of 54.5% at 80°C, a swelling rate of 14.8% at 80°C, an ion conductivity of 178.4 mS / cm at 80°C, a tensile strength of 54.7 MPa, and an elongation at break of 13.5%; the cross-linked polybenzimidazole has the following chemical structure:

[0274] ;

[0275] Among them, x = y = z= 2, m+n+i=1, n+i=0.05;

[0276] Viscosity average molecular weight M of cross-linked polybenzimidazole η = 119402 g / mol‌.

[0277] The structural characteristics and functions of the prepared cross-linked polybenzimidazole anion exchange membrane PBI-6Br-Pip-DPip-2 are as follows: Similar to the structural characteristics of PBI-6Br-Pip-DPip-1, the difference from PBI-6Br-Pip-DPip-1 is that the alkyl chain of the dicationic crosslinker of PBI-6Br-Pip-DPip-2 is longer, so the free volume in AEM is relatively larger, the water absorption rate is relatively higher, and it is more conducive to ion migration, thereby improving ionic conductivity.

Claims

1. A cross-linked polybenzimidazole anion exchange membrane, characterized in that: The cross-linked polybenzimidazole has a chemical structure as shown in Formula I or Formula II; ; Formula I ; Formula II Among them, R is , or ; x=y=z=1 or x=y=z=2; in formula Ⅰ, m+n+i+j=1, 0.05≤n+i+j≤0.15; in formula Ⅱ, m+n+i=1, 0.05≤n+i≤0.

15.

2. A cross-linked polybenzimidazole anion exchange membrane according to claim 1, characterized in that: The water absorption of the cross-linked polybenzimidazole anion exchange membrane at 80°C is 45.2~54.5%, the swelling rate at 80°C is <15%, the ion conductivity at 80°C is 157.8~178.4mS / cm, the tensile strength is 54.6~55.9MPa, and the elongation at break is 11.7~13.5%.

3. The method for preparing a cross-linked polybenzimidazole anion exchange membrane according to claim 1, characterized in that: First, 2,3-epoxypropyltrimethylammonium chloride is added to a polybenzimidazole solution, and the mixture is reacted at 80-100°C for 12-48 hours. Then, a flexible dicationic crosslinking agent and NaH are added to the reaction solution, and the mixture is reacted at 80-100°C for 12-48 hours. The reaction solution is precipitated in ethyl acetate, and the crosslinked polybenzimidazole is obtained by filtering, washing with ethanol, and drying. Finally, the crosslinked polybenzimidazole is dissolved to form a casting solution, and after drying to form a film, the film is soaked and washed with a KOH solution or a NaOH solution to obtain a crosslinked polybenzimidazole anion exchange membrane. Alternatively, first, 2,3-epoxypropyltrimethylammonium chloride is added to a polybenzimidazole solution, and the mixture is reacted at 80-100° C. for 12-48 hours, and the reaction solution is precipitated in ethyl acetate, filtered, washed with ethanol, and dried to obtain a grafted polybenzimidazole, and then the grafted polybenzimidazole is dissolved to form a casting solution, and after drying to form a film, the film is placed in an ethanol solution of a flexible dicationic crosslinker and NaH, and reacted at 80-100° C. for 12-48 hours, and then soaked and washed with a KOH solution or a NaOH solution to obtain a cross-linked polybenzimidazole anion exchange membrane; The molar ratio of 2,3-epoxypropyltrimethylammonium chloride to polybenzimidazole is 2-3:1, the molar ratio of the flexible dicationic crosslinker to polybenzimidazole is 1-3:10, and the molar ratio of NaH to the flexible dicationic crosslinker is 1-3:1; The flexible dicationic crosslinker is DBH-1, DBH-2, DPy-1, DPy-2, DPip-1 or DPip-2; The chemical formulas of DBH-1, DBH-2, DPy-1, DPy-2, DPip-1 and DPip-2 are as follows: ; ; ; ; ; 。 4. The method for preparing a cross-linked polybenzimidazole anion exchange membrane according to claim 1, characterized in that: First, add long side chain piperidine quaternary ammonium salt and NaH to the polybenzimidazole solution, and react at 80-100°C for 12-48h; then add a flexible dicationic crosslinker to the solution after the reaction, and react at 80-100°C for 12-48h, precipitate the reaction solution in ethyl acetate, filter, wash with ethanol and dry to obtain a cross-linked polybenzimidazole, and finally dissolve the cross-linked polybenzimidazole to form a casting solution, dry to form a membrane, and then soak and wash with a KOH solution or a NaOH solution to obtain a cross-linked polybenzimidazole anion exchange membrane; or First, add long side chain piperidine quaternary ammonium salt and NaH to the polybenzimidazole solution, react at 80-100°C for 12-48h, precipitate the reaction solution in ethyl acetate, filter, wash with ethanol and dry to obtain grafted polybenzimidazole, then dissolve the grafted polybenzimidazole to form a casting solution, dry the film, place it in an ethanol solution of a flexible dicationic crosslinker and NaH, react at 80-100°C for 12-48h, and then soak and wash with a KOH solution or a NaOH solution to obtain a cross-linked polybenzimidazole anion exchange membrane; The molar ratio of the long side chain piperidine quaternary ammonium salt to the polybenzimidazole is 2-3:1, the molar ratio of the flexible dicationic crosslinker to the polybenzimidazole is 1-3:10, and the molar ratio of NaH to the polybenzimidazole is 2-3:1; The synthesis method of the long side chain piperidine quaternary ammonium salt is as follows: 1,6-dibromohexane is dissolved in ethyl acetate, N-methylpiperidine is added dropwise at a rate of 0.05 mL per 2 seconds under stirring at room temperature, and then the mixture is reacted at 30-50° C. for 36-72 hours, and then the white precipitate in the reaction solution is filtered, washed and dried to obtain the long side chain piperidine quaternary ammonium salt; The molar ratio of 1,6-dibromohexane to N-methylpiperidine is 2-4:1, and the concentration of the solution obtained by dissolving 1,6-dibromohexane in ethyl acetate is 1.0-2.0 mol / L; The flexible dicationic crosslinker is DBH-1, DBH-2, DPy-1, DPy-2, DPip-1 or DPip-2; The chemical formulas of DBH-1, DBH-2, DPy-1, DPy-2, DPip-1 and DPip-2 are as follows: ; ; ; ; ; 。 5. The method for preparing a cross-linked polybenzimidazole anion exchange membrane according to claim 3 or 4, characterized in that: The synthesis method of DBH-1 or DBH-2 is as follows: dissolving dibromide A in acetonitrile to obtain a dibromide A solution, dissolving tetramethyldiamine in acetonitrile to obtain a tetramethyldiamine solution, adding the tetramethyldiamine solution to the dibromide A solution, reacting at 60-80° C. for 12-36 hours, filtering the reaction solution and collecting the filtrate, then drying the filtrate using a rotary evaporator to obtain a white powder, washing with ether and drying to obtain a flexible dicationic crosslinking agent DBH-1 or DBH-2; Dibromide A is 1,5-dibromopentane or 1,6-dibromohexane; Tetramethyldiamine is N,N,N,N-tetramethyl-1,6-hexanediamine or N1,N1,N8,N8-tetramethyloctane-1,8-diamine; The molar ratio of dibromide A to tetramethyldiamine is 5-10:1, the concentration of dibromide A solution is 0.5-0.7 mol / L, and the concentration of tetramethyldiamine solution is 0.2-0.3 mol / L.

6. The method for preparing a cross-linked polybenzimidazole anion exchange membrane according to claim 3 or 4, characterized in that: The synthesis method of DPy-1, DPy-2, DPip-1 or DPip-2 is as follows: dissolving tetrahydropyrrole and K2CO3, or piperidine and K2CO3 in ethanol, heating to 60-90°C and stirring, then adding an ethanol solution of dibromide B to the obtained solution, and continuing to stir and react for 48-72 hours, then pouring the obtained reaction solution into deionized water, extracting with ethyl acetate 2-4 times, then drying with Na2SO4 and filtering, collecting the organic phase and rotary evaporating with a rotary evaporator to obtain a yellow liquid, dissolving the yellow liquid and 1,5-dibromopentane or 1,6-dibromohexane in an amount of 2-4 times the mole of the yellow liquid in acetonitrile, stirring at 60-90°C for 24-48 hours, precipitating with ether after the reaction to obtain a white solid, washing with ether 2-4 times, and vacuum drying for 24-48 hours to obtain a flexible dicationic crosslinker DPy-1, DPy-2, DPip-1 or DPip-2; Dibromide B is 1,6-dibromohexane or 1,8-dibromooctane; The molar ratio of tetrahydropyrrole or piperidine to dibromide B is 2-4:1, and the molar ratio of K2CO3 to tetrahydropyrrole or piperidine is 1-2:1; in the solution obtained by dissolving tetrahydropyrrole and K2CO3, or piperidine and K2CO3 in ethanol, the concentration of tetrahydropyrrole or piperidine is 1.0-2.0 mol / L; the concentration of the ethanol solution of dibromide B is 0.5-1.0 mol / L.

7. The method for preparing a cross-linked polybenzimidazole anion exchange membrane according to claim 3 or 4, characterized in that: The polybenzimidazole solution is obtained by adding polybenzimidazole to dimethyl sulfoxide and then dissolving the polybenzimidazole at 60 to 80°C.

8. The method for preparing a cross-linked polybenzimidazole anion exchange membrane according to claim 7, characterized in that: The concentration of the polybenzimidazole solution is 2~5wt%.

9. The method for preparing a cross-linked polybenzimidazole anion exchange membrane according to claim 3 or 4, characterized in that: The casting solution is obtained by dissolving cross-linked polybenzimidazole in dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, and the concentration of the casting solution is 2-5wt%.

10. The method for preparing a cross-linked polybenzimidazole anion exchange membrane according to claim 3 or 4, characterized in that: The drying temperature is 60~100℃.

Citation Information

Patent Citations

  • Polybenzimidazole with side ammonium groups and anion exchange membrane thereof, and preparation methods thereof

    CN108623806A

  • Polysulfone cross-linked polybenzimidazole interpenetrating network anion exchange membrane as well as preparation method and application thereof

    CN117964932A

  • Long-side-chain polybenzimidazole anion membrane and preparation method thereof

    CN109830725A

  • Long-lateral-chain quaternarized polybenzimidazole cross-linked membrane and preparation method therefor

    CN110564150A